Exploring Children’s Creative Self-Efficacy Affected by After-School Program and Parent–Child Relationships - Liang, Chen-Chu; Yuan, Yu-Hsi (Frontiers in psychology, 2020)
This study aimed to verify the relationship among children's creative self-efficacy, parenting style, parent-child relationship, and after-school program. Judgmental sampling was used for subject selection from Taiwan. There are 550 valid participants composed of elementary school to junior high school students; their data were put into the statistical process. The multiple regression analysis was applied in this study. The survey tool was developed based on literature review and related articles. Research result supported the idea that the after-school program was the most significant variable that affected the student's creative self-efficacy. The "punitive discipline" and "autonomy support" of parenting style can affect positive parent-child relationships as well as students' creative self-efficacy. Evidence supported the notion that "negative parent-child relationships" will not motivate students' creative self-efficacy. Besides, the after-school program plays an important role in the students' creative self-efficacy independently.This study aimed to verify the relationship among children's creative self-efficacy, parenting style, parent-child relationship, and after-school program. Judgmental sampling was used for subject selection from Taiwan. There are 550 valid participants composed of elementary school to junior high school students; their data were put into the statistical process. The multiple regression analysis was applied in this study. The survey tool was developed based on literature review and related articles. Research result supported the idea that the after-school program was the most significant variable that affected the student's creative self-efficacy. The "punitive discipline" and "autonomy support" of parenting style can affect positive parent-child relationships as well as students' creative self-efficacy. Evidence supported the notion that "negative parent-child relationships" will not motivate students' creative self-efficacy. Besides, the after-school program plays an important role in the students' creative self-efficacy independently.